Odpowiedzi

2010-02-26T20:29:19+01:00
A)2a+2a-2b=4a-2b
b)-4x+(-2x)+4y+1=-6x+4y+1
c)-6x+8x-2y+x=3x-2y
d)-2x+3y+5x-5y+1=3x-2y+1
e)7a+9b+(-4x)-5b-4=4b+7a+(-4x)-4
f)-0,5x-0,2y+x+0,7y+1=0,5x+0,5y
1 1 1
Najlepsza Odpowiedź!
2010-02-27T00:00:56+01:00
A)
2a+(2a-2b)=
2a+2a-2b=
4a-2b

b)
-4x+(-2x+4y+1)=
-4x-2x+4y+1=
-6x+4y+1

c)
-6x+(8x-2y+x)=
-6x+8x-2y+x=
3x-2y

d)
(-2x+3y)+(5x-5y+1)=
-2x+3y+5x-5y+1=
3x-2y+1

e)
(7a+9b)+(-4x-5b-4)=
7a+9b-4x-5b-4=
7a+4b-4x-4


f)
(-0,5x-0,2y)+(x+0,7y+1)=
-0,5x-0,2y+x+0,7y+1=
0,5x+0,5y+1
1 5 1